2019
DOI: 10.1101/798876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Whole genome sequencing of 358 brown planthoppers uncovers the landscape of their migration and dispersal worldwide

Abstract: The brown planthopper (BPH), Nilaparvata lugens, is a serious migratory rice pest, which is distributed in the broad area of the tropical and temperate Asian-Pacific region. However, we know little about key aspects regarding its evolution such as how they diverged and dispersed worldwide. By resequencing and analyzing 358 BPH genomes from 92 populations across the world, we uncover the genetic relationships among their worldwide populations and the history of their global dispersal. We recovered five genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 23 publications
(22 reference statements)
1
20
0
Order By: Relevance
“…Moreover, the fall armyworm in Myanmar was first detected on maize plants in the Mandalay and Ayeyawaddy Regions in late 2018 or early 2019, and these regions are on, or close to, the coast [ 25 ], thus reinforcing the view that fall armyworm migrate into Myanmar from India by crossing the Bay of Bengal. Recent studies have reported that there are frequent genetic exchanges in migratory insects between southern India and southern China, such as the brown planthopper ( Nilaparvata lugens ) [ 26 ] and tobacco cutworm ( Spodoptera litura ) [ 27 ], and this also suggests that insects can migrate from southern India into southern China. It should be emphasized that southern India is suitable for these insect species.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fall armyworm in Myanmar was first detected on maize plants in the Mandalay and Ayeyawaddy Regions in late 2018 or early 2019, and these regions are on, or close to, the coast [ 25 ], thus reinforcing the view that fall armyworm migrate into Myanmar from India by crossing the Bay of Bengal. Recent studies have reported that there are frequent genetic exchanges in migratory insects between southern India and southern China, such as the brown planthopper ( Nilaparvata lugens ) [ 26 ] and tobacco cutworm ( Spodoptera litura ) [ 27 ], and this also suggests that insects can migrate from southern India into southern China. It should be emphasized that southern India is suitable for these insect species.…”
Section: Discussionmentioning
confidence: 99%
“…This supposition is supported by phenotypic differences between brown planthopper from the two regions, such as distinct virulence levels against resistant rice strains [80]. A recent analysis indicates that the South East / East Asian and South Asian clades are somewhat genetically divergent, but that there is a greater degree of gene flow between the two groups than was previously suspected [79]. In particular, brown planthopper from Myanmar, Yunnan (southwest China), Thailand and Laos showed a high degree of ancestry from South Asia, but all samples from the South East / East Asian range had experienced some gene flow from South Asian populations [79].…”
Section: Non-directed Migrationsmentioning
confidence: 85%
“…Further entomological radar [87], genetic [40,41,63,79], stable isotope [11,15,28,42] and individual marking [35,88] studies carried out in other regions and biomes of the world are needed to answer questions about the level of connectivity in insect migration systems. An exciting recent development is the reduction in weight of electronic tagging devices [89] which may help to get better flightpath data for very large insects (such as green darner dragonflies [65,67]), although it will take time to build up a database of migratory tracks (such as those emerging from decades of bird tagging).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations